Hyperbilirubinemia Protects against Aging-Associated Inflammation and Metabolic Deterioration - Zelenka, Jaroslav; Dvořák, Aleš; Alán, Lukáš; Zadinová, Marie; Haluzík, Martin; Vítek, Libor (Oxidative medicine and cellular longevity, 2016)
Mild constitutive hyperbilirubinemia is associated with a reduced risk of cardiovascular diseases, diabetes, and cancer. Since these pathologies are associated with aging, inflammation, and oxidative stress, we investigated whether hyperbilirubinemia interferes with ROS homeostasis in cell cultures and with inflammation, senescence, and mitochondrial dysfunction in aged rats. Human embryonic kidney cells and rat primary fibroblasts showed a dose-dependent decrease in the ratio of oxidized/reduced glutathione, intracellular H2O2 levels, and mitochondrial ROS production, with increasing bilirubin concentrations in the culture media. Compared to their normobilirubinemic siblings, aged hyperbilirubinemic Gunn rats showed significantly smaller amounts of visceral fat, better glucose tolerance, and decreased serum levels of proinflammatory cytokines TNFα, IL-1β, and IL-18. Simultaneously, livers from Gunn rats showed decreased expression of senescence markers and cell cycle inhibitors p21 and p16. Mitochondria from aged Gunn rats showed higher respiration and lower H2O2 production compared to controls. In conclusion, we demonstrated that mildly elevated serum bilirubin is generally associated with attenuation of oxidative stress and with better anthropometric parameters, decreased inflammatory status, increased glucose tolerance, fewer signs of cellular senescence, and enhanced mitochondrial function in aged rats.
Keywords: hyperbilirubinemie; Cells, Cultured; Mitochondria; Rats, Gunn; zvířata; Hyperbilirubinemia; zánět; intracelulární prostor; potkani Gunn; Reactive Oxygen Species; mitochondrie; bilirubin; Intracellular Space; Aging; metabolické nemoci; kultivované buňky; reaktivní formy kyslíku; Bilirubin; Inflammation; Animals; Metabolic Diseases; fibroblasty; Fibroblasts; stárnutí